Аргументативний потенціал прецедентних феноменів у політичному дискурсі - Одарчук, Наталія Андріївна; Мірончук, Тетяна Андріївна; Odarchuk, N. A.; Mironchuk, T. A. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті досліджено прецедентні феномени в політичному дискурсі. Представлено власне розуміння прецедентного тексту як підвиду прецедентного феномену й виокремлено його основні властивості. На матеріалі промов американського політика Гілларі Родем Клінтон розглянуто аргументативний потенціал прецедентних феноменів, тобто їх роль у здійсненні сугестивного впливу на отримувача інформації через внесення змін до його ціннісної системи. Precedent phenomena in political discourse are the object of investigation of the given article. It presents authors’ own understanding of the precedent texts as a kind of the precedent phenomena and singles out their main properties. On the material of the American politician Hillary R. Clinton’s speeches the argumentative potential of the precedent phenomena is analyzed, namely the role of the latter in making a suggestive influence on the recipient by means of modifying his evaluative system. Text reminiscences make it possible to increase the informativity of the utterance since referring to another text the speaker is able to transmit a greater amount of information using minimal means for its verbalization. Besides, precedent phenomena serve as the way of augmenting expressiveness and emotional richness of the discourse.
Argumentative Potential of the Precedent Phenomena in Political Discourse
Keywords: прецедентний феномен; precedent phenomenon; політичний дискурс; political discourse; аргументація; argumentation